Sans bords : distance et démocratie dans Letters from Iceland de W.H. Auden et Louis MacNeice - Regard, Frédéric (Études britanniques contemporaines, 2017)
Letters from Iceland presents itself as a form of distantiation: it relates the burlesque summer adventures of the poets in Iceland, while the ghost of the Spanish War insists to come back on the stage. I focus more particularly on the photographs provided by Auden and MacNeice to illustrate their account, and I argue that those images are in fact part of a more global aesthetic strategy enabling Auden to ‘take a position’ – not sides –regarding what is taking place in Europe. This is an idea partly suggested to me by Georges Didi-Huberman’s Quand les images prennent position (‘When Images Take a Position’), in which he deals with the aesthetics of montage in the Thirties. En tant que récit d’une aventure estivale burlesque en Islande, alors que rôde le spectre de la Guerre d’Espagne, Letters from Iceland constitue une « prise de distance ». Mon attention se porte en particulier sur les images fournies par Auden et MacNeice pour illustrer leur périple. Je tente néanmoins de montrer de quelle manière le dispositif qu’elles contribuent à mettre en place permet en réalité au poète de « prendre position » – et non parti – par rapport à ce qui se joue alors en Europe. L’idée m’est en partie suggérée par l’ouvrage de Georges Didi-Huberman, Quand les images prennent position, consacré à l’esthétique du montage dans les années 30.